2018
DOI: 10.3389/fimmu.2018.01293
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Modulation of Pregnancy-Related Immune Responses

Abstract: Progesterone (P4) is an important steroid hormone for the establishment and maintenance of pregnancy and its functional withdrawal in reproductive tissue is linked with the onset of parturition. However, the effects of P4 on adaptive immune responses are poorly understood. In this study, we took a novel approach by comparing the effects of P4 supplementation longitudinally, with treatment using a P4 antagonist mifepristone (RU486) in mid-trimester pregnancies. Thus, we were able to demonstrate the immune-modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 86 publications
4
52
0
7
Order By: Relevance
“…Considering that pro-inflammatory cytokines are associated with recurrent pregnancy loss on the one hand [17][18][19][20][21][22][23][24][25] and that progesterone has interesting immunomodulatory capabilities, [35][36][37][38] it stands to reason that progestogens can be considered for downregulating Th1/pro-inflammatory cytokine reactivity.…”
Section: Modulation Of Cytokine Profiles By Progestogensmentioning
confidence: 99%
“…Considering that pro-inflammatory cytokines are associated with recurrent pregnancy loss on the one hand [17][18][19][20][21][22][23][24][25] and that progesterone has interesting immunomodulatory capabilities, [35][36][37][38] it stands to reason that progestogens can be considered for downregulating Th1/pro-inflammatory cytokine reactivity.…”
Section: Modulation Of Cytokine Profiles By Progestogensmentioning
confidence: 99%
“…We have previously shown that CD4 and CD8 T cell activation, proportions of effector memory T cells expression CD28, Th17 and Treg proportions and some DC and NK cell subsets, all vary during the course of pregnancy (19). Therefore, Data is presented as mean ± standard error of the mean (SEM) or median ± interquartile range (IQR) as appropriate for the distribution normality.…”
Section: Flow-cytometry Based Leukocyte Phenotypingmentioning
confidence: 99%
“…In the context of influenza A, these DC confer resistance to infection and show improved anti-viral type I IFN production (64). We have previously shown that proportions of mDC and CD83 + mDC do not significantly change during pregnancy (19,65). Therefore, our findings may reflect pregnancy- (30,69,70).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations